Evaluation of rationality of fixed dose combinations of antimicrobials available in Indian market - Srivastava, Rohan; Kantharia, N. D. (International Journal of Basic & Clinical Pharmacology, 2022)
Background: The antimicrobial resistance is alarming at present. One of the important factors for resistance is use of irrational fixed dose combinations. Thus, objective was to critically analyze the rationality of FDCs of antimicrobial agents currently available in India. Methods: The FDCs of AMAs enlisted in Indian Drug Review 2019 were analyzed by 8 point criteria tool. Analysis includes number of active pharmacological ingredients, approval by central drug standard control organization, listing in world health organization model list of essential medicines (2019) or Government of India national list of essential medicines (2015). Literature search was used for assessing efficacy, safety, pharmacokinetic and pharmacodynamic interactions and advantages of each FDC. Each criterion was assigned score one, if positive and minus one, if negative leading to total score of 12. FDC with score of ≥7 was considered as rational. Results: The FDCs of AMA available in Indian market were 116 while FDCs included in WHO model list, 2019 were 24. Majority of FDCs available were irrational that include combination of antibacterial with bromhexine, carbocisteine, ambroxol, serratiopeptidase, antiamoebic and antifungal etc. Most of the rational FDCs belong to antiretroviral, antitubercular and antimalarial drugs. Conclusions: Most of the FDCs of AMAs available in Indian market are irrational. These needs educating the prescribers including resident doctors. There is need to critically review such FDCs by drug regulators with strict action regarding manufacturing and marketing.